What is XR? Towards a Framework for Augmented and Virtual Reality. (August 2022) - Rauschnabel, Philipp A.; Felix, Reto; Hinsch, Chris; Shahab, Hamza; Alt, Florian
Abstract: Augmented Reality (AR), Virtual Reality (VR), Mixed Reality, and Extended Reality (often – misleadingly – abbreviated as XR) are commonly used terms to describe how technologies generate or modify reality. However, academics and professionals have been inconsistent in their use of these terms. This has led to conceptual confusion and unclear demarcations. Inspired by prior research and qualitative insights from XR professionals, we discuss the meaning and definitions of various terms and organize them in our proposed framework. As a result, we conclude that (1) XR should not be used to connote extended reality, but as a more open approach where the X implies the unknown variable: xReality; (2) AR and VR have fundamental differences and thus should be treated as different experiences; (3) AR experiences can be described on a continuum ranging from assisted reality to mixed reality (based on the level of local presence); and (4), VR experiences can be conceptualized on a telepresence-continuum ranging from atomistic to holistic VR. Highlights: XR should not be used as an abbreviation for "Extended Reality"; X should be the placeholder for "all" new reality formats. AR and VR have fundamental differences and thus should be treated as different experiences. AR experiences can be described on a LOCAL PRESENCE continuum ranging from Assisted Reality to Mixed Reality. VR experiences can be conceptualized on a TELEPRESENCE-continuum ranging from atomistic to holistic VR.